Implementasi Metode Naive Bayes untuk Diagnosa Pengidap Demam Berdarah pada Kelurahan Antasan Besar berbasis Web - Akhmad Wahyu Redhani; Nurul Hidayat; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Dengue Hemorrhagic Fever (DHF) is one of the public health problems in Indonesia where the number of sufferers tends to increase and its distribution is getting wider, especially for the Antasan Besar sub-district. The use of web-based technology systems in assisting the diagnosis of dengue fever is currently very necessary. The system that is built to get accurate diagnostic results requires a method. The Naive Bayes method is one of the techniques that can be used to perform analysis in determining the diagnostic results from a number of data studied with the aim of producing optimal results. The use of the Naive Bayes method in this application is due to the probability that the accuracy value of the Nave Bayes method is close to the accuracy value of the experts. In this study, 3 trials were conducted using 4 test data and the results showed that based on the three experiments, the accuracy values ​​ranged from 96% to 97%, indicating that the classification accuracy has a small error value. So the classification using Naive Bayes in this study can be applied to determine the classification of the incidence of dengue hemorrhagic fever.